Does one effect size fit all? The case against default effect sizes for sport and exercise science - Caldwell, A. R.; Vigotsky, A. D. (SportRxiv Preprints, 2020)
Recent discussions in the sport and exercise science community have focused on the appropriate use and reporting of effect sizes. Sport and exercise scientists often analyze repeated-measures data, from which mean differences are reported. To aid the interpretation of these data, standardized mean differences (SMD) are commonly reported as description of effect size. The use of SMDs has been criticized by sport and exercise scientists as well as those in other disciplines. However, we believe, when thoughtfully applied, SMDs can be a useful analytical tool for sport and exercise scientists. In this manuscript, we hope to alleviate some confusion by demonstrating how effect sizes - primarily SMDs - are calculated, and describing their statistical properties. Finally, we provide high-level recommendations for how sport and exercise scientists can thoughtfully report raw effect sizes, SMDs, or other effect sizes for their own studies. The code to reproduce all analyses and figures within the manuscript can be found at the following link: https://www.doi.org/10.17605/OSF.IO/FC5XW.